Shift-life interactive art: mixed-reality artificial ecosystem simulation - Ch'ng, Eugene; Harrison, Dew; Moore, Samantha (Massachusetts Institute of Technology Press, 2018)
This article presents a detailed design, development and implementation of a Mixed Reality Art-Science collaboration project which was exhibited during Darwin’s bicentenary exhibition at Shrewsbury, England. As an artist-led project the concerns of the artist were paramount, and this article presents Shift-Life as part of an on-going exploration into the parallels between the non-linear human thinking process and computation using semantic association to link items into ideas, and ideas into holistic concepts. Our art explores perceptions and states of mind as we move our attention between the simulated world of the computer and the real-world we inhabit, which means that any viewer engagement is participatory rather than passive. From a Mixed Reality point of view, the lead author intends to explore the convergence of the physical and virtual, therefore the formalization of the Mixed Reality system, focusing on the integration of artificial life, ecology, physical sensors and participant interaction through an interface of physical props. It is common for digital media artists to allow viewers to activate a work either through a computer screen via direct keyboard or mouse manipulation, or through immersive means to activate their work, for “Shift-Life” the artist was concerned with a direct “relational” approach where viewers would intuitively engage with the installation’s everyday objects, and with each other, to fully experience the piece. The Mixed Reality system is mediated via physical environmental sensors, which affect the virtual environment and autonomous agents, which in turn reacts and is expressed as virtual pixels projected onto a physical surface. The tangible hands-on interface proved to be instinctive, attractive and informative on many levels, delivering a good example of collaboration between the Arts and Science.